Waste Glass Reuse in Foamed Alkali-Activated Binders Production: Technical and Environmental Assessment - Ruan, Shaoqin; Kastiukas, Gediminas; Liang, Shuang; Zhou, Xiangming (Frontiers in Materials, 2020)
Abstract: Waste glass is a type of construction and demolition waste (CDW), which carries significant environmental burdens and can be recycled. In this study, a foamed alkali-activated glass (FAAG) via the use of milled waste glass was synthesized in low-temperature (i.e., 80 ⁰C). The influence of foaming agent (i.e., aluminum powder) content on the foaming process of samples was investigated and optimized in view of their performance. The optimum mix formulation, which is FAAG with 10% aluminum powder was then selected, and followed by the measurement of the water-resistance and absorption, impact resistance and thermal conductivity of the prepared FAAG. X-ray diffraction was also involved to identify the phase formation within the samples. Finally, the environmental impacts related to the preparation of 1 kg FAAG were obtained. Results shows that a type of more sustainable FAAG compared with the commercial product was successfully developed in low-temperature, revealing the low thermal conductivity of ~0.13 W/(m∙K) with a density of ~0.59 g/cm3 and compressive strength of ~5.52 MPa, which is 97% higher than the commercial product. Meanwhile, in addition to a foaming agent, aluminum powder is also acting as a key component in the geopolymerization of samples, facilitating the formation of aluminosilicate that provides strength.